CONSTRUCTION OF SAFE AND HEALTHY ADOBE HOUSES AFTER THE PISCO 2007 EARTHQUAKE IN PERU - Blondet, Marcial; Vargas, Julio; Rubiños, Álvaro (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
On August 15th, 2007, a great earthquake of magnitude 7.9 Mw affected the southern area of Peru. Almost 76 thousand houses were destroyed and more than 319 thousand persons were affected. The majority of the destroyed constructions were made with adobe and the reason for their collapse was the lack of seismic reinforcement. Without any knowledge of healthy and earthquake resistant technologies, the affected families would rebuild their houses in a seismically vulnerable and unhealthy way. This paper presents the actions taken in the affected zones by the Catholic University of Peru (PUCP) in a joint effort with several cooperation agencies and NGOs to develop capacities and train dwellers on the construction of healthy and earthquake-resistant adobe houses. The improved adobe houses include seismic reinforcement based on a geomesh which completely covers all adobe walls. The geomesh reinforcement increases the stiffness and strength of the walls and, more importantly, maintains the integrity of the house after the adobe walls have cracked, thus avoiding collapse (Blondet et al., 2008). The sanitary conditions of the new adobe houses are enhanced by including an external dry hole latrine and an improved kitchen made with local materials. Training was provided to the dwellers of three cities in the affected area, including the construction of three improved adobe houses. It is hoped that the training program contributed to reduce the seismic risk and to improve the quality of life of many families in the areas affected by the Pisco earthquake. Furthermore, it is expected that these positive results will help disseminate the improved technologies for the construction of safe and healthy adobe houses in other seismic regions of Peru.